Ethnopharmacological insights and clinical prospects of ten Indonesian medicinal plants for pregnancy, postpartum, and lactation: a systematic review - Sanjaya, I Nyoman Hariyasa; Andonotopo, Wiku; Bachnas, Muhammad Adrianes; Dewantiningrum, Julian; Pramono, Mochammad Besari Adi; Mulyana, Ryan Saktika; Pangkahila, Evert Solomon; Akbar, Muhammad Ilham Aldika; Rahardjo, Theresia Monica; Suryawan, Aloysius; Rahardjo, Bambang; Yeni, Cut Meurah; Aldiansyah, Dudy; Bernolian, Nuswil; Wiradnyana, Anak Agung Gede Putra; Sulistyowati, Sri; Stanojevic, Milan; Kurjak, Asim (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2025)
Background: The perinatal period involves significant physiological and metabolic transitions, particularly concerning hypertensive disorders, preeclampsia, hemorrhage, lactation challenges, and oxidative stress. Although pharmacological therapies are available, their safety and accessibility remain inconsistent, especially in resource-limited settings. Indonesia’s extensive biodiversity and deep-rooted ethnomedicinal traditions offer promising yet underutilized botanical alternatives. This study aimed to review the efficacy of Indonesian medicinal plants used in pregnancy, postpartum, and lactation. Methods: This systematic review investigates ten Indonesian medicinal plants traditionally used during pregnancy, postpartum recovery, and lactation: Sauropus androgynus, Curcuma longa, Moringa oleifera, Nigella sativa, Centella asiatica, Orthosiphon aristatus, Syzygium polyanthum, Andrographis paniculata, Solanum nigrum, and Zingiber officinale. Literature from 2000 to 2025 was reviewed using PRISMA guidelines across global and regional databases. Phytochemical composition, mechanisms of action, therapeutic effects (e.g., antihypertensive, antidiabetic, galactagogue, hemostatic, antioxidant), and clinical relevance were critically evaluated. Results: All ten plants demonstrated pharmacological potential relevant to perinatal health challenges. Notably, Zingiber officinale offers antiemetic and anti-inflammatory benefits during early pregnancy, complementing the lactogenic, antihypertensive, and wound-healing properties of other species. However, gaps persist in human trials, dosage standardization, and regulatory oversight. Conclusion: The review highlights the importance of integrating validated traditional botanicals into perinatal care through interdisciplinary research, targeted clinical trials, and culturally responsive health policies. Bridging ethnopharmacology with maternal health systems offers a scalable, sustainable pathway toward maternal wellness and equity in Indonesia and comparable global settings.